Impact of living kidney donation on blood pressure and arterial stiffness: Systematic review and meta-analysis - Maria Smyrli; Theodora Oikonomaki; Chrysanthi Skalioti; Eleni Kapsia; Ioannis N. Boletis; Smaragdi Marinaki (PLoS ONE, 2025)
Background We aimed to conduct a systematic review and meta-analysis (PROSPERO CRD42023480478) regarding the impact of kidney donation on arterial stiffness indices such as pulse wave velocity (PWV) and augmentation index (AIx), along with its effect on blood pressure. Methods We searched for publications related to kidney/renal donors, arterial stiffness, blood pressure, and cardiovascular risk, and included every study employing those terms. A p-value < 0.05 was considered statistically significant. Results Twelve studies and 2059 individuals, with a mean age of 46.53 ± 11.27 years, were included in the analysis. Male donors constituted 40.6% of the participants, and the mean follow-up was 2.62 ± 3.2 years. Eleven studies indicated that systolic (SBP) and diastolic blood pressure remained stable within the first year after nephrectomy. However, as the follow-up period extended, especially beyond one year, both were increased (median difference (MD) of SBP was 2.09 [0.06, 4.12] over the first year and 7.7 [6.96, 8.44] over the 5 years of follow-up). Regarding PWV and AIx, assessed in 6 studies, no fluctuations were observed post-donation (MD of PWV was 0.1620 [−0.0423; 0.3662], and MD of AIx was 8.2265 [3.6450; 12.8080]). In addition, 11 studies revealed a decline in the estimated glomerular filtration rate (eGFR) after nephrectomy (MD −27.4960, p-value < 0.0001), though no albuminuria was observed. Lastly, BMI demonstrated negligible changes throughout the follow-up. Conclusion Kidney donation is a relatively safe procedure, and despite the observed decline in eGFR, it does not per se impose further cardiovascular burden on the donors. However, the heterogeneity and the lack of data underscores the need for high-quality studies so as to elucidate the connection between arterial stiffness, blood pressure, and GFR level.